MALAY CULTURAL LANDSCAPE STUDY TO IMPROVE THE IDENTITY OF MEDAN CITY - Hafni Dewi Nasution; . Nurhayati; Aris Munandar (http://arl.faperta.ipb.ac.id/, 2018)
Medan city which is now inhabited by multi-ethnic society provide cultural influence on indigenous people and led to demands that greater space requirements and varied, original identity that reflects the value of a city is difficult to identify. These conditions pose a threat to the city of Medan to be getting away from the Malay identity as a civilized nation. This study aims to identify the philosophy and character of the Malay cultural landscape in the city of Medan, analyze relevant landscape value and provide conservation strategies in the cultural landscape in the city of Medan. The research location is the Medan city field to historical research methods and Analytical Hierarchy Process (AHP). The analysis shows the highest value is in the component historic area (0.238). Furthermore Landmark (0.159), the Culture activity (0.115), Public Space (0.083), lane Circulation (0.074), RTH (0.075), landuse (0,066), Time series (0.066), Borders (0.067), Architecture (0.057) . Preservation strategy is the establishment of district Maimun Palace, Taman Sri deli and Al Mahsun become a cultural heritage area inseparable.